Carvedilol among Patients with Heart Failure with a Cocaine-use Disorder - Banerji, Dahlia (JACC Heart Fail, 2019)
OBJECTIVES: To assess the safety of carvedilol among heart failure (HF) patients with a cocaine-use disorder (CUD). BACKGROUND: Although carvedilol is recommended among certain patients with heart failure (HF), the safety and efficacy of carvedilol among HF patients with a CUD is unknown. METHODS: This was a single center study of patients with HF hospitalization. Cocaine use was self-reported or defined as having a positive urine toxicology. Patients were stratified by carvedilol prescription. Subgroup analyses were performed by strata of ejection fraction (EF) (≤40%, 41-49%, ≥50%). Major adverse cardiovascular events (MACE) was defined as CV mortality and 30-day HF readmission. RESULTS: From a cohort of 2,578 patients hospitalized with HF in 2011, 503 patients with a CUD were identified, among whom 404 (80%) were prescribed carvedilol and 99 (20%) were not. Both groups had similar characteristics; however, those prescribed carvedilol had a lower LVEF, heart rate, admission and discharge NT-proBNP and more coronary artery disease. Over a median follow-up of 19 months, there were 169 MACE events. MACE was similar between the carvedilol and the non-carvedilol groups (32 vs. 38%, p=0.16), among those with a preserved EF (30 vs. 33%, p=0.48) and was lower among those with a reduced EF on carvedilol (34 vs. 58%, p=0.02). In a multivariate model, carvedilol use was associated with lower MACE among HF patients with a CUD (HR=0.67, CI=0.481–0.863). CONCLUSIONS: Our findings suggest that carvedilol is safe among HF patients with a CUD and may be effective among those with a reduced EF.